Investigating the transcriptomic profile of plants under abiotic stress - Eu, Jasmin Shi Min (Nanyang Technological University, 2024)
Climate change is amplifying the frequency and intensity of abiotic stresses experienced by plants, posing significant risks to agriculture and ecosystems. Despite advancements made in understanding plant stress responses, there remains a gap in the global gene expression dataset examining abiotic stress resistance mechanisms in Selaginella moellendorffii and Klebsormidium nitens, both are rising model organisms for evolutionary studies due to their positions in the evolutionary tree. This study investigates the impact of seven abiotic stresses - heat, cold, light, darkness, salt, mannitol, and nitrogen deficiency - on the phenotype of Selaginella moellendorffi to identify optimal stress conditions. Additionally, we analysed the transcriptomic profile of Klebsormidium nitens under these optimal stress conditions. Our findings revealed that media stresses induced more pronounced growth reduction in Selaginella compared to environmental stresses. Transcriptome data of Klebsormidium showed a significantly higher number of differentially expressed genes in response to environmental stresses compared to media stresses. Across biological processes, photosynthesis emerges as the sole process affected by all abiotic stresses. The insights gained from this transcriptomic analysis are instrumental in understanding plant stress resistance mechanisms and can guide future research on the transcriptional coordination of genes involved in stress response.